2006
DOI: 10.1063/1.2212275
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic surface microvortices for mixing and particle trapping

Abstract: We report a free-surface electrohydrodynamic flow phenomenon driven by an ionic wind mechanism induced by a high frequency gas-phase ac field ͑Ͼ10 kHz͒. Intense vortices Ͼ1 cm/s are generated above a critical voltage, beyond which the vortices break down to spawn off new vortex pairs leading to a cascade of vortices over a continuum of length scales; the mixing efficiency approaches a turbulent-like state. Colloidal particles are attracted and aggregated into planar crystal structures within the vortices by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 8 publications
1
44
0
1
Order By: Relevance
“…These vortices can be generated using the geometrical modification of the channel profile, 72,142 by acoustic streaming 143 or via electrokinetic methods, such as induced-charge electro-osmosis, 144 AC electro-osmosis, 145 and dielectrophoresis. 146,147 The optimum conditions for particle trapping in confined microvortex flows have been analyzed analytically and numerically by Liu et al 148 using the concepts of nonlinear dynamics. It has been shown that introducing non-hydrodynamic forces can substantially improve the efficiency of vortical, point, and ring traps.…”
Section: Vorticity Induced Trappingmentioning
confidence: 99%
“…These vortices can be generated using the geometrical modification of the channel profile, 72,142 by acoustic streaming 143 or via electrokinetic methods, such as induced-charge electro-osmosis, 144 AC electro-osmosis, 145 and dielectrophoresis. 146,147 The optimum conditions for particle trapping in confined microvortex flows have been analyzed analytically and numerically by Liu et al 148 using the concepts of nonlinear dynamics. It has been shown that introducing non-hydrodynamic forces can substantially improve the efficiency of vortical, point, and ring traps.…”
Section: Vorticity Induced Trappingmentioning
confidence: 99%
“…A detailed description of the theory can be found in recent reviews. 33,99 Coakley et al 100 and Yeo et al 101 demonstrated early work involving ultrasonic waves in microfluidic devices. Recently, sonic waves were used for fast pumping ͑1-10 cm/s͒ in microfluidic channels.…”
Section: Acoustic Trappingmentioning
confidence: 99%
“…This stream of ions, an ionic wind, is generated at the tip due to its sharpness and corona discharge effects. 21,22 As the ions are propelled from this sharp electrode, they collide with air molecules which in turn collide with the liquid surface, thus imparting their momentum onto the liquid interface. A continuous stream of ions from the electrode tip acts as a point source of momentum on the liquid interface, driving an interfacial flow.…”
Section: Ionic Wind Generationmentioning
confidence: 99%
“…It has been shown that the size, shape, direction of rotation, and angular velocity is dictated by the placement of the sharp electrode with respect to the liquid surface and the magnitude of the applied field. 21 With the electrode placed at the center, a symmetric system of equal sized vortices is produced, while an off-center placement makes one of the vortices dominant. For our purposes, a single dominating vortex is desired and consequently the sharp electrode is placed near the corner of the liquid bulk and suspended ϳ4 mm above the liquid surface.…”
Section: Ionic Wind Generationmentioning
confidence: 99%